2018
DOI: 10.13102/sociobiology.v65i3.1640
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Management of Acromyrmex octospinosus (Reich): How Botanical Insecticides and Fungicides Should Promote an Ecofriendly Control Strategy.

Abstract: The leaf-cutting ant Acromyrmex octospinosus (Reich) causes serious damage to crops and protected areas due to its foraging activity. The main method of control of this species consists of the use of synthetic insecticides that can lead to environmental damage and negative side effects on human health. Consequently, alternative strategies, such as biopesticides, are needed. Insecticide evaluation by ingestion assays was performed using A. octospinosus in vitro bioassay and laboratory nests. Chemical analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, compounds such as terpenoids, caryophyllene epoxide, nerolidol and kolaenol isolated from Hymenaea courbaril, Melampodium divaricatum and Vismia bacciferae exhibited insecticidal activity when workers were supplied with an artificial diet containing these compounds (Howard et al, 1988). Feeding artificial diets, Boulogne et al (2018) observed insecticidal activity of the seed extract of Mammea americana against Ac. octospinosus workers whose lethal concentration was close to that of Fipronil (0.03g.kg -1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, compounds such as terpenoids, caryophyllene epoxide, nerolidol and kolaenol isolated from Hymenaea courbaril, Melampodium divaricatum and Vismia bacciferae exhibited insecticidal activity when workers were supplied with an artificial diet containing these compounds (Howard et al, 1988). Feeding artificial diets, Boulogne et al (2018) observed insecticidal activity of the seed extract of Mammea americana against Ac. octospinosus workers whose lethal concentration was close to that of Fipronil (0.03g.kg -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that ricinoleic, oleic and linoleic acids are the toxic agents of Ricinus oil. Another compound is coumarin, identified in extracts of rue (Ruta graveolens), jimsonweed (Datura estramonium), Cordia verbenaceae, peppermint (Mentha pitanperita), goat weed (Ageratum conyzoides) and tropical apricot (M. americana), which is a potential insecticide for leaf-cutting ants (Araujo et al, 2008;Boulogne et al, 2018). Equisetum sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of efficacy of this bait may be due to its constituents, which are possibly acting and killing the worker ants too quickly. Plant extracts cause mortality of individual ants in the laboratory, but have failed to control nests, due to the absence of the delayed action (Boulogne et al, 2018). The contamination of the workers is higher during the handling and preparation of the material to incorporate it into the fungus garden, which takes a few hours (Andrade et al, 2002).…”
Section: Nest Mortalitymentioning
confidence: 99%
“…and Atta spp. (White, 1998;Grosman et al, 2002;Boulogne et al, 2018), but it is an active ingredient with slow action toxicity in just few concentration ranges, when compared with others, such as sulfluramid (Nagamoto et al, 2004). Rapid action, as previously discussed, is not desirable to control leaf-cutting ants because it compromises workers foraging, and the dissemination of the insecticide baits inside the nest (Gandra et al, 2016).…”
Section: Nest Mortalitymentioning
confidence: 99%